Analyze the Relationship between QWL and Organizational Citizenship Behavior Zabol University - Naser Khodizaee (Journal of Global Pharma Technology, 2017)
A high quality of work life (QWL) is essential for all organizations to continue to attract and retain employees. Quality of work life is a comprehensive program which is designated to increase employee satisfaction. In today’s society, improving the working life has been one of the main goals of the organization and staff and their working environment. Today, in modern management concept of quality of work life around the world has become a major social issue. While in past decades only on working life in search of new systems to help staff between work life and personal life balance so that they can communicate. Any improvement in the quality of work life programs organizational culture that promotes the growth and excellence in the organization's staff .Organization citizenship behavior also is one important sociological dimension of organizations. The purpose of current study is Analyze the relationship between QWL and organizational citizenship behavior Zabol University. Using table of Morgan the sample volume was estimated 159 people. The SPSS and multiple linear regression and Pearson Tests were used for data analysis and responding to the hypotheses, respectively. Test show that there is meaningful relationship between six dimensions with quality of work life and organizational citizenship behavior.Keywords: quality of work life, organizational citizenship behavior.